(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
Traditional healing practices are in rare use along city areas as there remains easy access to modern treatment system and drugs than cultural ones. The declining ethnomedicinal knowledge among youths is of great threat to this knowledge and their possible future scopes and aptitudes towards drug synthesis in near future. The present survey aimed to document the status of ethnomedicinal knowledge among school youths in city with multicultural people in the community. Study was carried out in five schools of three municipalities in Banke district. The mode of data collection was via questionnaire survey. Questionnaire was open ended and selection of youth was in such a way that both male, female of different ages was included. Plant and animal species of medicinal significance were listed with their parts used, uses, method and experience to those practices. In total 87 informants (47 female and 40 male) were participated in interview. The data were entered in Excel and analyses were made. In total 45 plant species belonging to 31 families and 21 animal species belonging to 16 families were known among youths for the treatment of 36 symptoms under 14 ailment categories. Furthermore, two types of mode of use were mentioned: oral (for 19 animal and 41 plant species) and topical (for 4 animal and 26 plant species). Among them oral consumption was higher for both cases of plant and animal species use. The herb was a common life form for reported medicinal plants (n=22) and few were shrubs and climbers (n= 5). While, in case of animal parts used, flesh (15) was quite common, followed by honey, wax, and urine (n=1). There were two preparation methods mentioned; the raw form was common for plants and the cooked one for animal products. Since every student participated actively in the interview, a common recommendation to similar species results in the smaller number of species enumeration was interesting. It shows sharing of common traditional knowledge still in use at their own premises, repeatedly heard of. This survey implied to the existence and sharing of common traditional medicinal practices among youths in city areas. This work serves as a pioneer work to document ethnomedicinal knowledge among school youths in city areas. Furthermore, detailed interviews with parents and students of respective families may help to understand the status of inter-generational transmission of traditional healing practices and their future exploration to hidden opportunity and potential modernization with technology.